Experimental Study on the Performance of Air Source Heat Pump Water Heater over Wide-range Temperature Conditions - Wang Jijin; Qu Dehu; Ni Long; Yao Yang; Wang Jiagui (Zhileng xuebao)
Vapor compression air source heat pump (VCASHP) systems have been widely applied due to their simple structure and low initial cost. However, there are a series of problems when a VCASHP system is operated for space or water heating in cold regions. For example, with a decline of ambient temperature, the decreased heating capacity of the VCASHP system may be insufficient with respect to the consumer's requirement. Furthermore, its rising compression ratio may lead to an extremely high discharge temperature, resulting in shutting down. Therefore, a great deal of previous research into VCASHP systems has been carried out to address such problems. Nevertheless, the articles concentrated on VCASHP units with direct current (DC) speed regulation are scarce. In the present work, an air source heat pump water heater (5 HP) integrating flash-injection cooling, two-stage throttling, and DC speed regulation (DCAHP) that can be applied to cold and/or severely cold regions over wide-range temperature conditions, is proposed and studied experimentally. The results indicate that the proposed DCAHP performs well over a wide range of temperature conditions and reaches the heating capacity of 16548 W and 11278 W when the ambient dry bulb temperature is 7.0 and -20.0 oC, respectively. Furthermore, the heating energy efficiency ratio (EER) of the proposed DCAHP reached 3.0 and 1.6 individually. Specifically, the compressor input power tends to be reduced by 19% if the dimensionless distance between the thermometer of the expansion valve and the inlet of compressor is greater than 7/200 m/m; however, the valve capacity decline will be inevitable. While the area of evaporator was doubled, the heating capacity of the DCAHP rose by 18% at low ambient temperatures. In addition, the energy efficiency ratio of the DCAHP can be maximally enhanced by 50% with a subtle regulation of refrigeration oil volume of 3/20 kg/kg.